The pharmaceutical industry and saturated fat (Research, Society and Development, 2025)
The relationship between the pharmaceutical industry and the consumption of saturated fat has sparked increasing scientific and social interest, especially in light of the rise in non-communicable chronic diseases. Saturated fat, found in animal-based and ultra-processed foods, is widely associated with metabolic and cardiovascular disorders, which has direct implications for the pharmaceutical sector, responsible for producing medications aimed at treating these conditions. The objective was to analyze the relationship between saturated fat consumption and the role of the pharmaceutical industry in the prevention and treatment of associated diseases. The study is a literature review with a time frame from 2020 to 2025. The research was conducted using the Google Scholar, PubMed, and SciELO databases. Scientific articles in Portuguese, English, and Spanish that addressed clinical evidence and discussions about the economic and social impact of this relationship were selected. The analyzed studies indicated that high consumption of saturated fat contributes to increased rates of dyslipidemia and heart diseases, expanding the demand for cholesterol-lowering and antihypertensive medications. It was also noted that the pharmaceutical industry has been investing significantly in awareness campaigns and in the development of innovative therapies for lipid control. It is concluded that there is an interdependence between dietary patterns and the pharmaceutical market. Reducing saturated fat intake, combined with public prevention policies, can decrease the need for pharmacological treatments and promote collective health.